Superior Product Sales Strategy of UMKM in Desa Rejowinangun, Kecamatan Kademangan, Kabupaten Blitar Using Online Marketing Media - Putra, C. A.; R. Alit; Y. V. Via (Nusantara Science and Technology Proceedings)
Desa Rejowinangun is one of villages located in Kecamatan Kademangan, Kabupaten Blitar. This village has potential in form of Micro, Small and Medium Enterprises. In this village, majority of population make a living as traders or entrepreneurs, so that Desa Rejowinangun is dubbed as UMKM Village. Many of real problems faced by UMKM actors in this village. Most important problem is related to marketing of UMKM products. Business people in Desa Rejowinangun are still relying on conventional methods of carrying out marketing business so far. Using conventional sales model, many UMKM sell their products indirectly to consumers, but through orders or requests from distributors or stores. Production of UMKM, which were mostly sold to second hand, made UMKM not maximal in gaining production profits because profits had to be shared with second hand distributors. In an effort to increase economic value of UMKM in this village, there are ideas to develop economic values and marketing methods that utilize information technology and social media. One of them is sales strategy through online marketing and by utilizing social media. UMKM actors will get many benefits with production sales model directly to consumers, one of which is UMKM can sell their products directly to consumers with brands and packaging issued directly by producers. UMKM will have advantage of using information technology to increase economic value of UMKM in this village, which is expected to increase income and added value to Desa Rejowinangun as a UMKM village.